THE INFLUENCE OF CORPORATE GOVERNANCE AND FINANCIAL SUSTAINABILITY ON FIRM VALUE - Octaviani, Corine; Anam, A. Khoirul (Politeknik Negeri Ambon, 2025)
Introduction: This research focuses on listed companies in the food and beverage industry on the Indonesia Stock Exchange from 2018 to 2023. It examines the relationship between company value, corporate governance, and financial sustainability.Methods: Both factors significantly and positively affect company value, according to the findings of a quantitative study that used multiple linear regression analysis. The contribution of corporate governance, as assessed by the percentage of independent commissioners and the size of the audit committee, is more significant than that of financial sustainability, with the former contributing 8.322 and the latter 1.476, respectively.Results: The results show that the food and beverage industry in Indonesia is distinct from others in terms of financial performance volatility, governance practice consistency, and audit committee. This supports agency theory and a resource-based view. The implications of this study include recommendations for companies to enhance the composition of independent commissioners, strengthen the audit committee's function, and develop effective commodity risk management. Research limitations and suggestions for further studies are also comprehensively discussed.Conclusion: This study concludes that corporate governance and financial sustainability positively and significantly influence company value in the food and beverage sector listed on the Indonesia Stock Exchange from 2018 to 2023. For investors, these findings suggest prioritising the analysis of governance structure as a key indicator before considering long-term financial performance.Suggestion: Expand the research period to 10 years to obtain a more comprehensive picture, add moderating variables such as institutional ownership or CEO characteristics, and conduct comparative studies with other sectors with different characteristics. Expanding the scope of the study to include qualitative interviews with practitioners might uncover a more in-depth understanding of governance implementation at the operational level. Keywords: Corporate Governance, Financial Sustainability, Firm Value